AB0133 New evidence linking the in vivo implication of 4-hydroxynonenal in osteoarthritis pathogenesis. (23rd January 2014) - Shi, Q.; Fahmi, H.; Fernandes, J.C.; Benderdour, M.
Abstract : Background: 4-Hydroxynonenal (HNE) is one of the most abundant and reactive aldehydes of lipid peroxidation products and exerts various effects on intracellular and extracellular signalling cascades [1]. We have previously shown that HNE at low concentrations could be considered as an important mediator of catabolic and inflammatory processes in osteoarthritis (OA) [2, 3]. Objectives: To demonstrate the in vivo involvement of HNE in OA pathogenesis using experimental dog model of this disease. Methods: Protocol 1 - OA was induced by anterior cruciate ligament transection of the right knee in crossbred dogs. There were two experimental groups (n=4 dogs/group): placebo and carnosine (an HNE-trapping drug, 50 mg/kg/day) given orally for 8 weeks. Protocol 2 - Vehicle or pathophysiological dose of HNE (100 μM) were injected weekly into the right knee joint of crossbred dogs (n=4 dogs/group) for the entire duration of the study (16 weeks). We conducted macroscopic and histomorphological analyses of cartilage of the femoral condyles and/or tibial plateaus. We also conducted immunohistochemical analyses in cartilage explants for the following antigens: HNE, agrecannase-2, and matrix metalloproteinase -13 (MMP-13). Results: In the protocol 1, treatment with carnosine reduced the severity and histopathological score of OA cartilage lesions as well as the levels of HNE, MMP-13 and agrecannase-2 in cartilage explants. In the protocol 2, the intraarticular injection of HNE induced cartilage lesions on the tibial plateaus and femoral condyles with prominent osteophytes on lateral condyles. The expression of both MMP-13 and agrecannase-2 increased in cartilage explants from HNE-treated dogs. Conclusions: This is the first in vivo study to demonstrate the pathophysiological role of HNE in OA. The fact that carnosine abolishes HNE production and a number of factors known to be involved in OA pathogenesis renders it a clinically valuable agent in the prevention of this disease. References: Poli et al. Med Res Rev. 2008; 28:569-631. Morquette et al. Arthritis & Rheum 2006; 54(1):271-81. Vaillancourt et al. J Cell Biochem. 2007; 100(5):1217-31. Disclosure of Interest: None Declared